ویستی ئازاد و کردەی عەقڵانی: پێکگرتنی تیۆری و بنەڕەتە سیاسییەکانی عەقڵانیەتیی راوێژیی موعتەزیلە و دەوڵەتی ئەخلاقیی کانت - Sharafi, Dr. Idris Sheikh (Journal of Legal and Political Studies, 2025)
The emergence of freedom in the mind and the positioning of will in action is a topic worthy of attention in epistemology and political thought, to understand the reasons for the decline of rationality, the closure of spaces of freedom, and human subjugation in Islamic civilization, which possesses a history spanning several centuries. Approaching and comparing the epistemological and political foundations of two great schools - namely the Mu'tazila school, primarily represented by Judge Abd al-Jabbar al-Mu'tazili as a main theorist of this trend, and the critical idealism school headed by Immanuel Kant, which belong to different eras and distinct civilizations - opens the door to modern answers, especially regarding some fundamental human and political issues such as autonomy and will in the realm of action guided by reason. This leads us to conclude that the epistemological, intellectual, and political problems that have swept society today are, in essence, not related to the absence of necessary materials for progress toward rationality and freedom, and this is not an inevitable fate for this civilization from which escape is impossible, but rather relates to methodology, the context of realization, and the position of reason. The transcendental basis of reason as form and content of will in freedom makes it transcend the law of causality, and free will is not the result of any external cause. This is evident in the Mu'tazila's direct action (as opposed to generated action) and the thing-in-itself (nomena) in Kant, which becomes the basis of autonomy, where humans must be legislators for themselves and subject to categorical imperatives. The thesis of will in Mu'tazila and Kantian thought becomes a solid philosophical foundation for a political theory based on rationality and a democratic consultative contractual system, where will and action are directed toward good and establish a system compatible with universal ethics. The contractual system as consent of the people and ruler in Mu'tazila thought, if it does not fulfill its basic goals, paves the ground for rational revolution and considers it legitimate. However, regarding Kant's political system, the rule of law and constitution always takes priority over revolution, so Mu'tazila political thought is more radical than Kant's political philosophy. The ethical and political principles of Mu'tazila have universal value and represent a bright point in the history of Islamic civilization. However, the problem of philosophical crystallization caused infiltration into their intellectual system, and instead of transcending consciousness by defining the limits of authority's dominance and expanding the scope of freedom, they became an ideological apparatus of the state. When their creative ideas clashed with popular consciousness, people experienced a kind of alienation, and this led to collapse. In contrast to the Kantian project, which became the beginning of Western modernity and the modern state, establishing the rule of law and international institutions somewhat aligned with Kant's philosophical and ethical ideas. Keywords: Free Will, Rational Action, Universal ethic, state of right.
Keywords: Keywords Free Will; Rational Action; Universal ethic; state ofright